ANÁLISE EPISTEMOLÓGICA DAS TESES E DISSERTAÇÕES SOBRE ATENDIMENTO EDUCACIONAL ESPECIALIZADO: 2000 A 2009 - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2011)
This work has as its guiding question the theoretical and technical characteristics of theses and dissertations on special education service. Its general aim is to carry out an epistemological analysis of theses and dissertations on special education service written between 2000 and 2009, based on their theoretical and technical dimensions. Its specific aims include: a) To identify, describe and analyse the technical and theoretical characteristics of those theses and dissertations; b) To identify and analyse the types of methodological approach adopted in such works; c) To provide a reflection on the importance of praxis in such works. Following previously established criteria, 18 theses and dissertations were selected for the carrying out of the documentary analysis, which featured a qualitative approach and both quantitative and qualitative data. National and international laws on education, special education and special education service were used as theoretical references along with contributions from authors whose works are related to: a) Research on education, special education and special education service (GATTI, 2001; MARQUES et al., 2008; MARQUEZINE; TRAMONTINA, 2006; MENDES; NUNES; FERREIRA, 2002; MENDES et al., 2004; SÁNCHEZ GAMBOA, 1987, among others); b) Special education history and policy (BUENO, 1993; FERREIRA, 1991; FERREIRA; FERREIRA, 2004; JANNUZZI, 2006; MAZZOTTA, 1996; MENDES, 2006, among others); c) Epistemology applied to education research (LIMA, 2001; SANTOS FILHO; SÁNCHEZ GAMBOA, 2007; SÁNCHEZ GAMBOA, 1987, 2007); and d) Conceptions of the theory-practice relationship and scientific rigour (ANDRÉ, 2001; NORONHA, 2005; SOUZA; RAMOS, 2010; SÁNCHEZ GAMBOA, 1987, 2003, 2007, 2010a, 2010b, among others). The results indicate that most of the researches on special education service can not be characterised or classified by a particular methodological approach because they have a hybrid aspect and are not limited to any methodological boundary. The theory-practice relationship should be better defined by researchers in the field so that they can move forward in the understanding of the importance of praxis in their researches and produce works that are synonymous with transformation rather than just reports on reality.
Epistemological analysis of theses and dissertations on special education service: 2000 to 2009
Keywords: Educação especial; Atendimento educacional especializado; epistemologia; produção científica; Práxis; Special education; Special education service; epistemology; scientific production; praxis; CNPQ::CIENCIAS HUMANAS::EDUCACAO